Rhizosphere heterogeneity shapes abundance and activity of sulfur-oxidizing bacteria in vegetated salt marsh sediments - Thomas, François; Giblin, Anne E.; Cardon, Zoe G.; Sievert, Stefan M. (Frontiers in Microbiology, 2014)
Salt marshes are highly productive ecosystems hosting an intense sulfur (S) cycle, yet little is known about S-oxidizing microorganisms in these ecosystems. Here, we studied the diversity and transcriptional activity of S-oxidizers in salt marsh sediments colonized by the plant Spartina alterniflora, and assessed variations with sediment depth and small-scale compartments within the rhizosphere. We combined next-generation amplicon sequencing of 16S rDNA and rRNA libraries with phylogenetic analyses of marker genes for two S-oxidation pathways (soxB and rdsrAB). Gene and transcript numbers of soxB and rdsrAB phylotypes were quantified simultaneously, using newly designed (RT)-qPCR assays. We identified a diverse assemblage of S-oxidizers, with Chromatiales and Thiotrichales being dominant. The detection of transcripts from S-oxidizers was mostly confined to the upper 5 cm sediments, following the expected distribution of root biomass. A common pool of species dominated by Gammaproteobacteria transcribed S-oxidation genes across roots, rhizosphere, and surrounding sediment compartments, with rdsrAB transcripts prevailing over soxB. However, the root environment fine-tuned the abundance and transcriptional activity of the S-oxidizing community. In particular, the global transcription of soxB was higher on the roots compared to mix and rhizosphere samples. Furthermore, the contribution of Epsilonproteobacteria-related S-oxidizers tended to increase on Spartina roots compared to surrounding sediments. These data shed light on the under-studied oxidative part of the sulfur cycle in salt marsh sediments and indicate small-scale heterogeneities are important factors shaping abundance and potential activity of S-oxidizers in the rhizosphere.